"The truth is not in the middle": Journalistic norms of climate change bloggers. (November 2019) - van Eck, Christel W.; Mulder, Bob C.; Dewulf, Art
Highlights: Most traditional journalistic norms are also supported by climate change bloggers. Climate change bloggers do not support the journalistic norm balance. Climate change bloggers identify additional journalistic norms. Truth, comprising objectivity, transparency and honesty, is a salient norm for these bloggers. Climate sceptic and mainstream bloggers support similar journalistic norms. Climate change has often been presented in a biased way in traditional media outlets, due to journalists' adherence to the norm of balanced reporting. More generally, journalistic norms shape the selection and composition of news and thereby influence how climate change is covered in traditional media. Climate change coverage is also prominent in new media outlets, such as blogs. The current research aims to identify which journalistic norms are supported in the climate blogosphere, on the basis of 27 interviews with climate change bloggers. The results show that climate change bloggers support the traditional journalistic norms of personalization, dramatization, novelty, authority and order, but not balance. Beyond the traditional journalistic norms, climate change bloggers identify contextualization, clarity, decency, and particularly truth as important journalistic norms. Truth is understood as a multi-dimensional norm comprising objectivity, transparency, and honesty. No differences are identified between norms supported by climate sceptical and climate mainstream bloggers, but each group operationalizes the norms differently. These results challenge and redefine traditional models of journalistic norms, and contribute to theorizing how journalistic norms shape climate change coverage in new media outlets. As such, this research on climate change bloggers and their journalistic norms is crucial for a fuller understanding of current climate change communications.